Foundation of website of sports prescription based on expert system - Sun, Q.-Z.; Shao, G.-H.; Liu, M.-H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Good health and long life are the aims people always pursue. But recently, with the decrease of necessary exercise, the constitution of human beings is showing a tendency to decline in China. That`s why more and more people need sports prescriptions so as to strengthen the constitution and overcome illnesses. However, since sports prescriptions are made by sports experts, the lack of experts on health protection will lead to dissatisfactory effects people got. So, it becomes an essential problem to popularize expert knowledge. The foundation of website of sports prescription based on expert system can make people get the sports prescription of their own through network securely, secretly conveniently and quickly, and in this way expert knowledge can be really popularized. Methods Computer processing,Knowledge engineering, literature review and expert symposiums. Results A flow chart of this system is shown.